Computational Study on Vibrational Properties of Thyroxine Molecule in Different Charge States - Dhital, S.; Pudasainee, K.; Lamichhane, H. P. (Journal of Nepal Physical Society, 2021)
The vibrational frequencies of thyroxine (T4) molecule are calculated through computational method and major modes of vibration are assigned to corresponding frequencies in this research work. First we took neutral isolated T4 molecule for our study, and then we extend our work to anion state. The shift produced in the frequency and IR intensities for different vibrational modes has been calculated for change in state from neutral to anion. In addition, the difference spectra for these two charge states has also been studied for the T4 molecule by adding the dimethyl sulfoxide (DMSO) solvent. Furthermore, the same calculations are performed for the isolated neutral T4 molecule with C13 labelling. All these calculations are carried out by density functional calculations with the B3LYP hybrid functional applying the SDD effective core potential basis set. The calculated geometrical parameters are in good agreement with the experimental results. Additionally, the calculated frequencies lies within the characteristic region belonging to the respective mode of vibrations.